THE INFLUENCE OF HAZARDOUS COSMETIC MATERIAL LITERACY AND GUIDELINE BOOK UTILIZATION ON COSMETIC SAFETY COMPETENCE - Dwi Atmanto; Eti Herawati; Aniesa Puspa Arum; Tri Handayani (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The increasing use of cosmetic products among Indonesian migrant workers enrolled in beauty training has highlighted concerns about limited awareness of hazardous ingredients and insufficient safety skills, particularly in managing toxic substances and cosmetic packaging waste. This study investigated the effects of hazardous cosmetic material literacy and guideline book utilization on cosmetic safety competence among 30 Indonesian migrant trainees at the Gayantri Training Center in Singapore. Participants received structured instruction supported by a practical guideline covering hazard identification, safe handling, storage, and environmentally responsible waste management. A quantitative associative design was employed, and the data were analyzed using multiple linear regression at an α = 5% significance level. The resulting equation was (Y = 12.457 + 0.428X1 + 0.391X2 + e). Hazardous cosmetic material literacy significantly predicted safety competence (t = 3.842, p = 0.001), indicating that stronger knowledge improved participants’ ability to recognize and manage hazardous cosmetic substances. Guideline book utilization also had a significant effect (t = 3.516, p = 0.002). Collectively, both variables significantly influenced cosmetic safety competence (F = 24.638, p = 0.001) and explained 64.7% of its variance (R2 = 0.647). These findings demonstrate that literacy-based training and practical guidance can strengthen safe, professional, and environmentally responsible cosmetic practices